Analisis Keamanan Informasi PT. Indofood Sukses Makmur, Tbk : Studi Kasus tentang Peran Objek Vital, Pengamanan File, dan Pengamanan Cyber - Edy Susanto; Alvionita Dairo Lende; Akmal Riza Firjatullah; Reza Almasyah Pratama (Universitas Kristen Indonesia Toraja, 2023)
Information security analysis of PT. Indofood is a case study that discusses the role of vital objects, file security, and cyber security in the company. PT. Indofood is a large company in the food and beverage industry, which faces significant information security challenges. In terms of vital objects, PT. Indofood identifies critical systems and infrastructure that must be strictly protected. A risk evaluation may have been carried out to identify potential threats and take appropriate steps to protect these vital objects. Access controls, physical safeguards, and security training may have been put in place to keep vital objects safe. File security is an important focus for PT. Indofood. Security measures implemented include access control, data encryption, regular backup and restore, and monitoring of file activity. Strict access control policies and security awareness training provide additional protection for critical company files. In cyber security, PT. Indofood uses various measures to protect their systems and networks from cyberthreats. Implementation of firewalls, network protection systems, and regular software updates helps prevent unauthorized access and keeps systems secure. Email security solutions, identity and access management, and data encryption provide an additional layer of protection against cyberattacks. High security awareness and security awareness training provided to employees helps reduce attack risk and improve response to security incidents. PT. Indofood also conducts periodic security tests to identify vulnerabilities in their systems and take necessary remedial actions. Overall, PT. Indofood has implemented strong measures in securing vital objects, file security, and cyber security. However, it is important to remember that information security is an ongoing endeavor that must be continuously updated according to the latest developments in security and technological threats.